2013
DOI: 10.1371/journal.pone.0071759
|View full text |Cite|
|
Sign up to set email alerts
|

Mangiferin Prevents Guinea Pig Tracheal Contraction via Activation of the Nitric Oxide-Cyclic GMP Pathway

Abstract: Previous studies have described the antispasmodic effect of mangiferin, a natural glucoside xanthone (2-C-β-Dgluco-pyranosyl-1,3,6,7-tetrahydroxyxanthone) that is present in mango trees and other plants, but its mechanism of action remains unknown. The aim of this study was to examine the potential contribution of the nitric oxide-cyclic GMP pathway to the antispasmodic effect of mangiferin on isolated tracheal rings preparations. The functional effect of mangiferin on allergic and non-allergic contraction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…In that study mangiferin was also reported to restore the level of eNOS, while the eNOS/iNOS ratio was perturbed in the ischemia reperfusion model of rats. In various other studies regarding the gastro protective effect of mangiferin, it is observed that besides disruption of the redox environment in the gastric tissue, I/R insult enhances the activity of different proinflammatory modulators . It was observed that mangiferin significantly reduces the level of IL‐1β, E‐selectin, and neutrophil infiltration, exhibiting its immunomodulatory and anti‐inflammatory effect .…”
Section: Role Of Mangiferin On Several Inflammatory Pathways In Some mentioning
confidence: 94%
See 2 more Smart Citations
“…In that study mangiferin was also reported to restore the level of eNOS, while the eNOS/iNOS ratio was perturbed in the ischemia reperfusion model of rats. In various other studies regarding the gastro protective effect of mangiferin, it is observed that besides disruption of the redox environment in the gastric tissue, I/R insult enhances the activity of different proinflammatory modulators . It was observed that mangiferin significantly reduces the level of IL‐1β, E‐selectin, and neutrophil infiltration, exhibiting its immunomodulatory and anti‐inflammatory effect .…”
Section: Role Of Mangiferin On Several Inflammatory Pathways In Some mentioning
confidence: 94%
“…Moreover, in acute lung injury, mangiferin is capable in alleviating the inflammatory responses by down regulating the MAP kinase signaling pathways . In addition, mangiferin also exhibits antispasmodic effects by activating the nitric oxide‐cyclic GMP pathway and thereby preventing tracheal contractions is guinea pig . Mangiferin by upregulating heme oxygenase‐1 dose dependently, alleviates lung injury in septic mice models.…”
Section: Effect Of Mangiferin Against Inflammation Related Organ Dysfmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the epithelium capacity to provide factors to relax the smooth muscle is firmly established. These factors include nitric oxide (NO), carbon monoxide, PGE 2 and prostacyclin, which protect the airway from excessive bronchoconstriction (Barnes 1998, de Sousa et al 2010, Billington et al 2013, Vieira et al 2013. We tested several inhibitors to identify which factors produced by epithelial cells could be involved in the antispasmogenic activity of glucagon in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Mangiferin exerts protective effects against bronchial asthma and other allergic diseases. Research has demonstrated that mangiferin inhibits tracheal contractions induced by distinct stimuli, including allergens, histamine, 5-hydroxytryptamine and carbachol, in a dose-dependent manner (95). The antispasmodic effect of mangiferin on allergic and non-allergic tracheal contraction of guinea pig tracheal rings are a result of increased intracellular levels of nitric oxide synthase 3 and cyclic GMP (95).…”
Section: Other Properties Of Mangiferinmentioning
confidence: 99%